CD40-CD40L Interactions Induce Chemokine Expression by Human Microglia : Implications for Human Immunodeficiency Virus Encephalitis and Multiple Sclerosis - D’Aversa, Teresa G. (American Society for Investigative Pathology, 2002)
CD40 is a protein on microglia that is up-regulated with interferon (IFN)-γ and is engaged by CD40L, found on CD4(+) T cells, B cells, and monocytes. These interactions may be important in central nervous system inflammatory diseases. Microglia have been shown to be a source of chemokines, whose expression plays a key role in central nervous system pathologies. We examined the expression of CD40 on microglia in human immunodeficiency virus (HIV) encephalitic brain, and the effects of CD40-CD40L interactions on the expression of chemokines by cultured microglia. We found significantly increased numbers of CD40-positive microglia in HIV-infected brain tissue. Treatment of cultured microglia with IFN-γ and CD40L increased expression of several chemokines. IFN-γ- and CD40L-induced MCP-1 protein was mediated by activation of the ERK1/2 MAPK pathway, and Western blot analysis demonstrated phosphorylation of ERK1/2 upon stimulation of microglia. In contrast, IFN-γ- and CD40L-induced IP-10 protein production was mediated by the p38 MAPK pathway. Our data suggest a mechanism whereby CD40L+ cells can induce microglia to secrete chemokines, amplifying inflammatory processes seen in HIV encephalitis and multiple sclerosis, and implicate CD40-CD40L interactions as a target for interventional strategies.